University of the Future: Re-Imagining Research and Higher Education 2020
DOI: 10.29117/quarfe.2020.0265
|View full text |Cite
|
Sign up to set email alerts
|

The Problems Facing Students of College of Education at Qatar University: A Path to Academic Accreditation

Abstract: This study aimed to reveal the most important problems facing students of the College of Education from their point of view and its relationship to some variables. The study used two tools: the first is the open interview (focus group), and the second is a questionnaire designed by the researcher. It contained 65 items distributed on six axes: costs and assignments, tests, academic professor, academic registration and guidance, the content of study materials, and finally the classrooms have been verified as be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Other research states that universities must ensure their students progress and achieve high performance by supporting and helping them improve their skills, knowledge, disposition and academic achievement. With graduation standards met, the college may get full accreditation (Fakhrou, 2020). Previous studies using the observation method and factor analysis with the SEM method identified a significant positive effect of leadership, competence, lecturer performance, and organizational climate on efforts to maximize university achievement in accordance with BAN-PT accreditation standards.…”
Section: Introductionmentioning
confidence: 99%
“…Other research states that universities must ensure their students progress and achieve high performance by supporting and helping them improve their skills, knowledge, disposition and academic achievement. With graduation standards met, the college may get full accreditation (Fakhrou, 2020). Previous studies using the observation method and factor analysis with the SEM method identified a significant positive effect of leadership, competence, lecturer performance, and organizational climate on efforts to maximize university achievement in accordance with BAN-PT accreditation standards.…”
Section: Introductionmentioning
confidence: 99%